Ending Cooperation: A Formal Model of Organizational Change in German Pharmaceutical Interest Representation - Andreas Broscheid (Max Planck Institute for the Study of Societies, 2005)
This paper uses a game theoretic model to investigate the 1993?94 split-up of the main German pharmaceutical association into an association for multinational, researchbased companies and an association representing small and medium-sized fi rms. In order to explain the breakdown of cooperation among group members, the paper employs a model that combines collective action and bargaining. The model suggests that changing issues can play an important role in organizational change. In the case of the German pharmaceutical industry, the key issue changed from pharmaceutical registration to cost control. With respect to the former issue, the different factions in the pharmaceutical industry had complementary interests and were able to fi nd a compromise position. The latter issue led to a confl ict over the redistribution of scarce resources between the factions; formally, this meant that all issue dimensions were equally important to all factions. As a result, it became impossible to realize policy gains through a political compromise. – – Die folgende Studie untersucht den Austritt forschender Arzneimittelhersteller aus dem Bundesverband der Pharmazeutischen Industrie (BPI) zum Jahreswechsel 1993/1994 und die darauf folgende Gründung des Verbands forschender Arzneimittelhersteller (VFA). Unter Zuhilfenahme eines spieltheoretischen Modells, das Verhandlungstheorie mit der Theorie kollektiven Handelns verbindet, wird hier argumentiert, dass Änderungen im Issuekontext organisatorischen Wandel verursachen können. Im Falle der deutschen Pharmainteressen wurde die Zulassung von Arzneimitteln als dominantes Issue von der Frage der Kostenkontrolle abgelöst. Im Falle der Arzneimittelzulassung konnten die verschiedenen Herstellergruppen Kompromisspositionen erreichen, während im Falle der Kostenkontrolle zu einem schwer lösbaren Verteilungskonflikt zwischen innovativen, OTC- und Nachahmerprodukt-Herstellern führte, der auf die Gründung getrennter Verbände hinauslief.
Keywords: 300